Dionysus and the Nymphs in a Forgotten Celebration “in the Demos”: Reflections on the Attic Theoinia - Valdés Guía, Miriam Amparo (ARYS. Antigüedad: Religiones y Sociedades, 2021)
In the Harpocración lexicon (s.v. Theoinion) a reference to a dispute between the Koironidai and Krokonidai gene in Lycurgus’ times is preserved and, in this context, Theoinia is defined as the feast of Dionysus in the demes (“kata demous”) in which the gennetai sacrifice. I intend to analyze this festival, which is probably part of the Athenian Anthesteria, but at a local / rural level. The objective is to see how the god of wine is celebrated in rural areas, and the role played by members of certain gene, as well as, in a broader perspective, many women from Attica, who celebrate the god of wine and new wine in close relationship with the cult of the Nymphs.